Application of Word Wall to Foster Students' Understanding of Science Learning - Chairul Bariyah; Andi Prastowo (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The development of technology has significantly benefited education. Technological tools make teaching and learning more engaging, provide broad access to information, and develop digital skills. It also supports better assessment and helps teachers and learners stay connected to these developments. Teachers must therefore master these skills if they are to create a learning environment that meets the demands of the times. The purpose of the research is to find out whether the application of wordwall as a learning media can foster students' understanding of SD Sardonoharjo 1 Ngglik. This research interviewed one of the teachers at the elementary school. The findings show that the application of wordwall in science learning in the fifth grade of SD Sardonoharjo 1 Ngglik is very useful to improve students' understanding of the subject matter, help students understand and remember science concepts better, and motivate students to participate in learning which is shown by actively responding and responding to questions.